BOOK REVIEW: LINN ULLMANN, "NELINIȘTE, (DE UROLIGE)”, TRADUCERE DE OVIO OLARU, IAȘI, EDITURA POLIROM, 2020, 367 P. - HODÂRNĂU, Ioana (Studia Universitatis Babeș-Bolyai Philologia, 2020)
The latest translation from Linn Ullmann, ˗ one of the most important voices in the contemporary Norwegian literature ˗ Neliniște (De urolige in the original Norwegian title), published by Editura Polirom in 2020, has previously been a success among the Scandinavian countries, being translated into sixteen languages and nominated at the Nordic Council Prize. This book tackles a variety of universal human experiences, from the problematic of memory and love to the perspective of death and its ways of manifestation. While the present novel can be considered a portrait of a missing father, Linn Ullmann’s prose is undoubtedly one that documents more than a single image, that of the celebrated figure of Ingmar Bergman, and opens the discussion over the valability of human interaction, the relationship between different generations and the possibility of living with the constant feeling of solitude.